2017
DOI: 10.18632/oncotarget.20479
|View full text |Cite
|
Sign up to set email alerts
|

Candidate tumor suppressor ZNF154 suppresses invasion and metastasis in NPC by inhibiting the EMT via Wnt/β-catenin signalling

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is especially prevalent in southeast Asia and southern China, but its molecular mechanisms remain poorly characterized. DNA methylation is associated with initiation and progression of tumors, including NPC. Through a genome-wide DNA methylation screening approach, we discovered ZNF154, but its methylation status and roles in NPC have not been investigated.MethodsThe methylation status of ZNF154 in NPC was detected with Methylation specific-PCR (MSP) and Quantitative Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Based on the aforementioned findings, we hypothesized that LHX2 may promote the progression of NPC. Further research revealed that existing literature had reported that the Wnt/β-catenin signaling pathway was closely related to the progression of NPC [2528]. Moreover, a few studies have documented that LHX2 mediates the Wnt/β-catenin signaling pathway in the development of disease [29, 30].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the aforementioned findings, we hypothesized that LHX2 may promote the progression of NPC. Further research revealed that existing literature had reported that the Wnt/β-catenin signaling pathway was closely related to the progression of NPC [2528]. Moreover, a few studies have documented that LHX2 mediates the Wnt/β-catenin signaling pathway in the development of disease [29, 30].…”
Section: Resultsmentioning
confidence: 99%
“…When we analyzed the patient data for the clinical course, we found a significant association between ZNF154 promoter hypermethylation and better postoperative survival (Figure 3, Table 2 and Table 3). A recent study has shown that ZNF154 methylation was associated with better survival in nasopharyngeal carcinoma [13]. In contrast, a different research group reported poor outcomes in loss of function of ZNF154 in prostate cancer [14].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a couple of studies have focused on how biomarkers regulate EMT in NPC (14,15). In addition, the aberrant activation of the Wnt/β-catenin pathway is commonly reported to be involved in the EMT process of NPC (16).…”
Section: Introductionmentioning
confidence: 99%